Effects of jigsaw and animation techniques on students' understanding of concepts and subjects in electrochemistry - Doymus, Kemal; Karacop, Ataman; Simsek, Umit (Educational technology research and development, 2010)
This study investigated the effect of jigsaw cooperative learning and animation versus traditional teaching methods on students' understanding of electrochemistry in a first-year general chemistry course. This study was carried out in three different classes in the department of primary science education during the 2007–2008 academic year. The first class was randomly assigned as the jigsaw group, the second as the animation group, and the third as the control group. Students participating in the jigsaw group were divided into five "home groups" since the topic electrochemistry is divided into five subtopics. Each of these home groups contained four students. The groups were as follows: (1) Home Group A (HGA), representing the fundamental concepts of electrochemistry, (2) Home Group B (HGB), representing the electrochemical cell and energy source, (3) Home Group C (HGC), representing electrolysis, (4) Home Group D (HGD), representing Faraday's laws, and (5) Home Group E (HGE), representing corrosion. The home groups broke apart, like pieces of a jigsaw puzzle, and the students moved into jigsaw groups consisting of members from the other home groups, who were each assigned a subtopic. For students in the animation group, their lesson focused on explaining the step-by-step process of electrochemistry through a computer-animated presentation. The main data collection tools were the Test of Scientific Reasoning and the Particulate Nature of Matter Evaluation Test. The results indicated that the jigsaw and animation groups achieved better results than the control group.